SIGMUND FREUD, 1856-1939 - Toegel, Christfried. ([S.l.])
1 online resource
Keywords: Sigmund Freud, 1856-1939 draws on a wide range of primary sources to present all the datable events that took place in Sigmund Freud's life, shining new light on his day-to-day experiences. Christfried Toegel's work provides details and context for the personal, social and political conditions under which Freud developed his theories during this time period. The book's timeline presents not only significant events but also the small and everyday interactions and experiences in Freud's life. Drawn from sources including Freud's calendars, notebooks, travel journals and lists of fees, letters and visits, this unique book provides unparalleled insight into his work. Sigmund Freud, 1856-1939 will be of great interest to psychoanalysts in practice and in training, as well as academics and scholars of Freud, psychoanalytic studies, the history of science and the history of Europe.